2014
DOI: 10.2218/jls.v1i2.1101
|View full text |Cite
|
Sign up to set email alerts
|

Knappable Materials in the Criș Valley, Romania

Abstract: Abstract:The purpose of this study is to identify and characterise some of the raw materials in the Criș Valley, in the Apuseni Mountains, Romania which are suitable for knapping tools. The materials cropping out in this area include: siliceous sinter, agate, and silicified wood. The basic characteristics of the materials, obtained by macroscopic and petrographic investigations, provide a reference database useful in provenance studies on individual artefacts or whole assemblages. An assessment of each materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The high quality materials are the same as those found throughout the Transylvanian basin -Carpathian obsidian, Miorcani type Moldavian flint, and Balkan flint. These materials are described in previous publications (Crandell 2008;2009b;2012a;2012b;2012c;2014a;2014b;in press;Crandell & Mărcuţi in press;Crandell et al 2013;Crandell & Popa 2015;Crandell & Vornicu 2015) so only a brief mention will be made here for the benefit of readers who have not read (or do not have access to) the previous publications. By identifying the sources of raw materials in region, it was possible to identify probable sources of the artefacts.…”
Section: Lithic Resourcesmentioning
confidence: 99%
“…The high quality materials are the same as those found throughout the Transylvanian basin -Carpathian obsidian, Miorcani type Moldavian flint, and Balkan flint. These materials are described in previous publications (Crandell 2008;2009b;2012a;2012b;2012c;2014a;2014b;in press;Crandell & Mărcuţi in press;Crandell et al 2013;Crandell & Popa 2015;Crandell & Vornicu 2015) so only a brief mention will be made here for the benefit of readers who have not read (or do not have access to) the previous publications. By identifying the sources of raw materials in region, it was possible to identify probable sources of the artefacts.…”
Section: Lithic Resourcesmentioning
confidence: 99%
“…Previous geological and archaeological research has indicated that siliceous rocks such as cherts, radiolarites, cherty limestones, and other knappable materials used in Prehistory originate from the Southern Apuseni Mts., particularly in the Metaliferi and the Trascǎu mountains (Crandell 2008;2014;Herz & Savu 1974;Lupu, 1995;Nicolae 1992). Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the past two decades have seen a substantial increase in petrographic analyses of lithic raw materials (e.g., Băltean et al . ; Crandell , , , ; Alexandrescu and Soare ; Cârciumaru et al . ; Crandell et al .…”
Section: Introductionmentioning
confidence: 99%